The Identity of the "Average" Lithuanian: Contradictions at the End of the Century - Subačius, Paulius (Sociologija. Mintis ir veiksmas, 1999)
The article aims to analyze the issues of the ‘average’ – in terms of age, social status and cultural experience – Lithuanian identity. The author suggests that the change of cultural models of identity creates a discontinuity between the structure of identity and the social life. He argues that the discontinuity is especially evident in the six dimensions of self-understanding: the interpretation of history, city, religious affiliations, national identity, power and community. The author argues that the tension is resolved in a model of identity that lacks a civic dimension.
Keywords: identity; societal cultural context; self-understanding